Study on Efficiency Improvement of Data Analysis in Customer Asset Allocatior - An, Chenyang (Journal of Computer, Signal, and System Research, 2025)
With the continuous development of the financial market, customers’ investment preferences and purchasing behaviors are evolving rapidly. Leveraging data analysis to enhance the efficiency and accuracy of customers’ asset allocation decisions has become a crucial technical approach in modern finance. This paper primarily focuses on the practical application and existing challenges of data analysis in customer asset management. Key issues, including fragmented data integration, inconsistent data quality, limited real-time processing capabilities, and suboptimal algorithm models, are thoroughly analyzed. In response, optimization strategies are proposed, such as establishing a unified data integration platform, strengthening data quality management mechanisms, and improving real-time data processing capabilities. By addressing these challenges, financial institutions can significantly enhance decision-making effectiveness, increase investment returns, and provide more reliable guidance for customers’ asset allocation. This study offers valuable insights for the development and refinement of data-driven strategies in the financial industry.